Safety of COVID-19 Vaccines and the Effect of COVID-19 Infection in Children with Milk Allergies - Kwon, Junghyun; Zhu, Catherine K.; Mule, Pasquale; Mazer, Bruce; McCusker, Christine; Beaudette, Liane; Lejtenyi, Duncan; Ke, Danbing; Ouamrane, Manel; Ben-Shoshan, Moshe (Archives of Clinical and Medical Case Reports, 2024)
This study investigates the safety of COVID-19 vaccines and infection in children with milk allergies. The cohort comprised 50 children with challenge-confirmed milk allergy undergoing oral immunotherapy. Among them, 90% received the first dose, and 88% received the second dose of COVID-19 vaccines (mainly BNT162b2). Results showed that 51.1% had no symptoms after the first dose, and 56.8% had no symptoms after the second dose. Common side effects included injection site reactions, flu like symptoms, and chest discomfort. None reported allergic reactions or respiratory symptoms. Interestingly, 64% of the children had a history of COVID-19 infection, mostly presenting flu-like symptoms. While the study suggests minimal risk for adverse reactions in children with milk allergies, the limitations, such as a small sample size and specificity to milk allergies, underscore the necessity for broader investigations. This research highlights the ongoing need to refine risk assessments and ensure the safety of COVID-19 vaccination across diverse pediatric populations.